THE TUTORSHIP FUNCTION: LIFELONG LEARNING AND TRANSITION PATHS - Chianese, Gina (PEOPLE: International Journal of Social Sciences, 2017)
Over the years, the role and function of the tutor is changed. The meaning of the term tutor saw the phasing out of security and protection sense to highlight a formative and educational significance. The tutor, metaphorically, acts a bit as “a modern Charon” ferries subjects-intraining in the transition paths: the analysis of the characteristics and competences, the identification of needs, the design of personal paths or orientation initial and ongoing. This seems, at a glance, to offer a multifaceted meaning of the term. Tutor is a person able to guide the subject-in-training in the path of the construction of knowledge and competences. At the same time, the tutor is a counsellor that “take care of” and a coach that lead people to go forward.